A Comparative study of alkali treated date palm fiber based brake friction composites and standard Kevlar‐based brake friction composites. Issue 1 (3rd November 2021) - Kumar, Naresh; Grewal, J. S.; Singh, Avtar; Mehta, Vikas
Abstract: Recently many research studies have revealed the increasing importance of natural fiber in modern applications. Natural fibers are used these days in many important sectors like medical, aerospace, agriculture, and so forth. The cause of increasing the application of natural fiber in different fields is its eco‐friendly behavior and excellent mechanical properties. In the research work, date palm, a natural fiber, is used to replace asbestos and Kevlar, which are very harmful to the human body. There are very few papers on comparative study of natural fiber‐based composites to actual brake friction material. In this study, new brake pad composites of date palm fiber are developed and compared with Kevlar‐based brake pad composites. The different percentages (5%–20%) of date palm fiber and Kevlar (5–10) were used to compare the study. The date palm fiber composites have given maximum better results on 5% composition for the mechanical, tribological, physical, and chemical proprieties.